Mercury methylation in boreal aquatic ecosystems under oxic conditions and climate change: a review - Rodríguez, Juanjo (Frontiers in Marine Science, 2023)
Methylmercury (MeHg) formation is a concerning environmental issue described in waters and sediments from multiple aquatic ecosystems. The genetic and metabolic bases of mercury (Hg) methylation have been well described in anoxic environments, but a number of factors seem to point towards alternative pathways potentially occurring in pelagic waters under oxic conditions. Boreal aquatic ecosystems are predicted to undergo increasing concentrations of dissolved organic matter (DOM) as a result of higher terrestrial runoff induced by climate change, which may have important implications in the formation of MeHg in the water column. In this review, different Hg methylation mechanisms postulated in the literature are discussed, with particular focus on potential pathways independent of the hgcAB gene pair and occurring under oxic conditions. Potential effects of DOM on Hg methylation and MeHg bioaccumulation are examined in the context of climate in boreal aquatic ecosystems. Furthermore, the implementation of meta-omic technologies and standardized methods into field measurements and incubation experiments is discussed as a valuable tool to determine taxonomic and functional aspects of Hg methylation in oxic waters and under climate change-induced conditions.